2005
DOI: 10.1097/01.prs.0000156333.57852.2f
|View full text |Cite
|
Sign up to set email alerts
|

A Volumetric Analysis of Soft-Tissue Changes in the Aging Midface Using High-Resolution MRI: Implications for Facial Rejuvenation

Abstract: The present study indicates that ptosis alone does not account for the changes observed in the aging midface. Selective hypertrophy of the upper portion of the cheek fat pad was also observed. The mimetic muscles, on the other hand, showed no significant differences with aging. To attain maximum precision in facial rejuvenation, these data suggest that after suspension of the ptotic cheek fat pad, each patient should be evaluated for excess bulk in the upper portion of the cheek fat pad. If excess bulk is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(104 citation statements)
references
References 25 publications
3
99
0
2
Order By: Relevance
“…[6][7][8][9][10][11][12]23 Other studies have examined age-related volumetric changes in the facial soft tissue and described an increase in the orbital fat and lower eyelid fat, as well as selective atrophy in the cheek fat associated with increasing patient age. 1,[24][25][26][27] While prior studies have described the repositioning of facial soft tissues and the volume changes in the facial fat as primary contributors to the appearance of an older face, it is also possible that specific, age-related changes in facial tissue properties also contribute to the findings associated with an older appearing face.…”
Section: Introductionmentioning
confidence: 79%
“…[6][7][8][9][10][11][12]23 Other studies have examined age-related volumetric changes in the facial soft tissue and described an increase in the orbital fat and lower eyelid fat, as well as selective atrophy in the cheek fat associated with increasing patient age. 1,[24][25][26][27] While prior studies have described the repositioning of facial soft tissues and the volume changes in the facial fat as primary contributors to the appearance of an older face, it is also possible that specific, age-related changes in facial tissue properties also contribute to the findings associated with an older appearing face.…”
Section: Introductionmentioning
confidence: 79%
“…Indeed, according to Gierloff et al, as the face ages, there is an inferior migration of the midfacial fat compartment [23]. Midface volume changes have been described using MRI, topography, and photography [24][25][26]. We also found that lower lid fat herniation and upper eyelid ptosis make the subject appear most tired.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, Gosain and colleagues revealed that the cheek fat pad is thickened and augmented in the elderly than in young subjects using 3D volumetric analysis of the facial magnetic resonance image. 17 In addition, this study revealed that there was a site specificity in midfacial fat thickening with aging. In an elderly subject's face, the infraorbital area (corresponding to the IO-lat and the IO-med) and the nasojugal area (NJsup, NJ-mid, and NJ-inf) are relatively elevated compared with the adjacent area (MC-lat and the MC-med: mid cheek depression).…”
Section: Discussionmentioning
confidence: 95%